Preliminary results of the degradation of platinum based catalyst in PEM fuel cells using PIXE - Gunther, Maria Virginia (2012)
This work reports the first results obtained on the dissolution and reprecipitation of platinum nanoparticles in the catalyst-membrane boundary of the MEA of a PEM fuel cell after 700 hours of operationunder open circuit conditions. The formation of a platinum line on the membrane side near the cathode will be monitored using the PIXE technique in the ion beam facility at Tandar. The MEA used in the experiment was acommercial one (E-TEK), having a Nafion membrane and nanoparticulated Pt catalyst (loading 40%) on both, anodic and cathodic sides. Details of the sample preparation, the operating fuel cell parameters and the cuttingprocedure of the MEA previous to the ion beam analysis are described. The spatial resolution of the technique is discussed, along with the importance of the results for modelling the catalyst degradation in PEM fuel cells.